The effects of nutrient deprivation on macroautophagic flux and chaperone-mediated autophagy in a model of alzheimer's disease - Ntsapi, Matlakala Claudia (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.